The development of a manufacturability analysis system for micro-milling - Abdul Shukor, Syaimak (2010)
Manufacturability analysis systems (MASs) have been developed to enable the evaluation of manufacturability aspects during the design stage. MASs have been shown to be useful for macro-manufacturing processes but less attention or effort has been put for their development in the scope of micro-manufacturing. This thesis describes the development of a MAS for a micro-machining domain (MicroMAS) with a custom-made 4-axis Miniature Machine Tool (MMT) being the scope of implementation.